Transforming Your Business into an Adaptive Entrepreneur in a Changing World - Hendayani, Baiq (JURNAL ILMIAH DETUBUYA, 2025)
This article discusses the urgency and critical role of business transformation in developing adaptive entrepreneurs who can navigate the ever-changing world. In an era of increasingly rapid globalization and digitalization, both companies and individuals face significant challenges to survive and thrive. Therefore, a new approach to running a business is needed that is more flexible, responsive to change, and oriented towards continuous innovation. This business transformation is not limited to product or service development, but also encompasses the development of adaptive skills essential to keep pace with rapid changes in markets, technology, and consumer consumption patterns. Ultimately, successful business transformation focuses not only on improving business strategy or technology, but also on creating a more holistic sustainability across all aspects of the company's operations. This requires a strong commitment from all elements within the organization to move towards a bigger vision, oriented towards long-term growth, and able to adapt to changes in a very dynamic business environment.